A progress of Public-Private Partnerships in São Paulo’s housing policy: challenges and conflicts in accessing decent housing - Moreira, Rebecca Moura; Sígolo, Leticia Moreira (National Journal of City Management, 2024)
The article aims to analyze the advancement of Public-Private Partnerships (PPPs) in housing for social interest in the central area of São Paulo. Based on a literature review and document research, it was found that such partnerships have presented limitations in providing housing for the low-income population, leading to conflicts and displacements in strategic areas of interest to the real estate market. This facilitates investor access to housing services and allows construction companies to use urban planning tools for economic exploitation and the mobilization of public lands in the city. Housing PPPs come in a context of weakened housing policies and increased private sector involvement in public services, driven by neoliberal thinking. This situation raises questions about the effectiveness of PPPs in meeting the needs of vulnerable populations living in inadequate or deficient housing. Financing difficulties for lower-income families and the displacements carried out for new housing developments have led to the relocation of local residents and workers, some of whom have been pushed into environmentally fragile and peripheral areas. As a result, there is a growing role of the private sector in decisions regarding the production of housing for social interest, which not only fails to extend its reach to the poorest groups but also creates problems related to urban density and urban sprawl. These issues need to be addressed to promote more just and sustainable cities in their social, environmental, and economic aspects, committed to reducing inequalities, socio-spatial segregation, and promoting democratic governance in cities.